The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/0886260518772106
|View full text |Cite
|
Sign up to set email alerts
|

A Thematic Analysis of the Impact of MY MASCULINITY HELPS as a Tool for Sexual Violence Prevention

Abstract: The purpose of this study is to explore the impact of an educational documentary, MY MASCULINITY HELPS ( MMH), as a sexual violence prevention tool. MMH is a short (i.e., 31 min) educational documentary that explores the role of African American men and boys in the prevention of sexual violence. Participants ( N = 88) completed an electronic, qualitative questionnaire after viewing the documentary and data collected were analyzed and interpreted using thematic analysis. Findings from the study highlighted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…RMA among high-risk fraternity members did not change significantly. Engaging men as allies in sexual violence prevention, a strategy that encompasses the development of positive social norms around masculinity, gender, and violence (Basile et al, 2016; Grimmett, Conley, Foster, & Clark, 2021), may also be a useful resource for this purpose. Hillenbrand-Gunn, Heppner, Mauch, and Park (2010) found that RMA by high school males declined at posttest as well as a 4-week follow-up after participating in a three-session program based on the “men as allies” approach.…”
Section: Discussionmentioning
confidence: 99%
“…RMA among high-risk fraternity members did not change significantly. Engaging men as allies in sexual violence prevention, a strategy that encompasses the development of positive social norms around masculinity, gender, and violence (Basile et al, 2016; Grimmett, Conley, Foster, & Clark, 2021), may also be a useful resource for this purpose. Hillenbrand-Gunn, Heppner, Mauch, and Park (2010) found that RMA by high school males declined at posttest as well as a 4-week follow-up after participating in a three-session program based on the “men as allies” approach.…”
Section: Discussionmentioning
confidence: 99%
“…A small but growing research base is measuring the social impact of documentary storytelling (Chattoo & Das, 2014;Grimmett et al, 2018;King et al, 2018;Nisbet & Aufderheide, 2009;Parikh Foxx et al, 2020). In 2011, the North Carolina Coalition Against Sexual Assault (NCCASA) was awarded a grant from the U.S. Department of Justice Office on Violence Against Women to engage Black men and boys in the prevention of sexual violence (Flood, 2011).…”
Section: My Masculinity Helpsmentioning
confidence: 99%
“…NCCASA then accepted a proposal from the first author to develop a short educational documentary to meet this objective. The result was My Masculinity Helps (MMH), a short film featuring Black males, designed to engage boys and men in the deconstruction of gender roles, masculinity, and power and in the prevention of sexual violence (Grimmett & Hambridge, 2013). The film specifically addresses rape myths and bystander intervention and demonstrates understanding and support for survivors of sexual violence.…”
Section: My Masculinity Helpsmentioning
confidence: 99%
See 2 more Smart Citations